If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = 11 + 0.5x Solving 17 = 11 + 0.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5x' to each side of the equation. 17 + -0.5x = 11 + 0.5x + -0.5x Combine like terms: 0.5x + -0.5x = 0.0 17 + -0.5x = 11 + 0.0 17 + -0.5x = 11 Add '-17' to each side of the equation. 17 + -17 + -0.5x = 11 + -17 Combine like terms: 17 + -17 = 0 0 + -0.5x = 11 + -17 -0.5x = 11 + -17 Combine like terms: 11 + -17 = -6 -0.5x = -6 Divide each side by '-0.5'. x = 12 Simplifying x = 12
| -4+2y=9 | | 9w-4(w-2)=3(w+1)-9 | | 12x+48=4 | | 9a-5a=8a | | 8x+7(x+2)=-1 | | 5b+11-2b= | | 5=(x+3)(x+3) | | 12t-4(t-5)=-4 | | -8-12q=-7-11q | | 9-2(y-3)=11 | | 2a+2a+2a=12a | | 6(s-4)+1=3s+7 | | (x-3)(x+4)-2(3x-2)=x^2+8x+16 | | x^2=-18x | | -8x+3=-2 | | 5x^3+50x^2=z | | 4p+1-5p=-8 | | 2-5[5m-5]=73 | | 4y/16+3.5=52.8-12.9 | | -3*4+9y=-57 | | 7x+3-3x=15 | | 5x+16=7x+21 | | 3(x^3)-(x^2)-75x+25=0 | | 7(x-9)=(2x+4) | | 4*-8+9y=14 | | (4-3x^2)(x^2+1)=2 | | 6x+4=-16 | | 4x(x-1)-(2x+5)(2x-5)=1 | | 5*10-y=54 | | -3*(-3)= | | d/7=-13 | | a/16=9 |